(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate some results of post-operative care after Robotic laparoscopic surgery based on some criteria such as recovery time, recovery stay, complication rate, mobility time, surgical wound condition and some factors related to care results. Materials and methods: Prospective cross-sectional descriptive study on 36 patients undergoing Robotic laparoscopic surgery from October 2023 to October 2024. Patients after Robotic laparoscopic surgery were cared for according to the post-operative patient care process and the evaluation criteria were recorded from the end of surgery until the patient was transferred to the Department of Abdominal Surgery 1. Results: The average age of the study subjects was 52.2±12, the highest was 75 years old, the lowest was 32 years old. The study subjects living in rural areas accounted for 66.7%, urban areas accounted for 33.3%, the study subjects were farmers, self-employed accounted for 80.2%. Postoperative patients with nausea and vomiting accounted for 20.6% Postoperative patients with abdominal distension accounted for 8.1%. The majority of patients with little postoperative pain accounted for 77.5%, good surgical wound condition (77.7%), the rest had average and poor surgical wound condition of 22.3, good mobility reached 80.6%. Postoperative complication rate in the study: 2.7%. Average recovery time was 14.6 minutes. Average recovery time was 159.8 ± 132 When the patient had cardiovascular disease or diabetes, the time spent in the recovery room increased, in the study tested by statistical test showed statistical significance with p < 0.01. Conclusion: Patients after Robotic laparoscopic surgery studied from January 2023 to October 2024 had a recovery time of 14.6 minutes, the average recovery room stay time was 159.8 ± 132. When the patient had cardiovascular disease or diabetes, the recovery room stay time increased, in the study tested by statistical test showed statistical significance with p < 0.01.